Antibacterial Effect of Bitter Leave (Vernonia amygdalina) on Klebsiella pneumoniae - Sa’idu, Haruna; Ahmad, Hassan Ismail; Olanrewaju, Salau Abiola; Mahmoud, Aisha Bello (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
High rate of multi drug resistance bacteria caused by Klebsiella pneumoniae is increasing day by day, which in turn becomes medical and economic important to humans. The present study investigates the antibacterial effect of bitter leaf on Klebsiella pneumoniae. Frothing test and agar well diffusion method was used in this study. The former method indicate the presence of phytochemicals such saponin, tannin, flavonoid, alkaloid and carbohydrate in the plant while the later method indicate the potential effect of the plant extract to inhibit the growth of Klebsiella pneumoniae under different concentration ranging 2.5, 5, 10 20 mg/mL. The various zones of inhibition obtained under these concentrations were 0.0±0, 7±0.8, 11±0.6 and 14.00±1.3 mm, respectively. The highest zone of inhibition recorded was 26.00±2.3 mm using control experiment whereby no activity was obtained using 2.5 mg/mL plant extract. Thus, increase in the concentrations of extract was found to inhibit the growth of the bacteria under study. This research reports the potential effect of Vernonia amygdalina on the activity of K. pneumoniae.